2015
DOI: 10.1038/bmt.2015.131
|View full text |Cite
|
Sign up to set email alerts
|

IV pentamidine for primary PJP prophylaxis in adults undergoing allogeneic hematopoietic progenitor cell transplant

Abstract: Abbreviations: ARA-C = cytosine arabinoside; ATG = antithymocyte globulins; Bu = busulfan; Clo = clofarabine; Cy = cyclophosphamide; Flu = fludarabine; Mel = melphalan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Although concerns had been raised in the past regarding reduced lung penetration of IV pentamidine, many of these studies demonstrated clinically equivalent efficacy compared with the aerosolized route, and thus, IV pentamidine is often preferred in the very young because of ease of delivery. 3,7,20,22,29,30 Weintrub et al 31 reported breakthrough of 14% in a small national survey about monthly IV pentamidine in pediatric HIV, and Gupta et al 32 reported 6% PCP breakthrough for q3-q4 weeks dosing in 30 children with HIV; both groups concluded IV pentamidine was acceptable as second-line prophylaxis for their populations with comparable breakthrough rates to other available options.…”
Section: Discussionmentioning
confidence: 99%
“…Although concerns had been raised in the past regarding reduced lung penetration of IV pentamidine, many of these studies demonstrated clinically equivalent efficacy compared with the aerosolized route, and thus, IV pentamidine is often preferred in the very young because of ease of delivery. 3,7,20,22,29,30 Weintrub et al 31 reported breakthrough of 14% in a small national survey about monthly IV pentamidine in pediatric HIV, and Gupta et al 32 reported 6% PCP breakthrough for q3-q4 weeks dosing in 30 children with HIV; both groups concluded IV pentamidine was acceptable as second-line prophylaxis for their populations with comparable breakthrough rates to other available options.…”
Section: Discussionmentioning
confidence: 99%
“…All patients underwent screening for vancomycin-resistant enterococcus colonization on the day of admission and they received antimicrobial prophylaxis with oral ciprofloxacin, fluconazole, and acyclovir starting Day-2 of transplant. They also received a dose of intravenous pentamidine (4 mg/kg) on admission to the hospital, as prophylaxis against Pneumocystis jirovecii pneumonia, and the intravenous pentamidine was repeated every 28 days, as described previously [12].…”
Section: Introductionmentioning
confidence: 99%
“…While TMP–SMX remains the gold standard for PJP prophylaxis, bone marrow toxicity is a limiting factor for its use in pediatric patients receiving tandem ASCT, who require adequate hematologic recovery between them. American and European guidelines suggest second‐line drugs such as inhaled pentamidine, dapsone, or atovaquone, with limited evidence . Some practicalities should be considered, related to equipment and facilities that may make using inhaled pentamidine difficult …”
mentioning
confidence: 99%
“…American and European guidelines suggest second‐line drugs such as inhaled pentamidine, dapsone, or atovaquone, with limited evidence . Some practicalities should be considered, related to equipment and facilities that may make using inhaled pentamidine difficult …”
mentioning
confidence: 99%
See 1 more Smart Citation